PELATIHAN CAKAP BERMEDIA DIGITAL DI KAWASAN ARGAPURA BUMI MANDIRI JABAR DIGITAL SERVICE DISKOMINFO JABAR - Ade Bastian; Dony Susandi; Harun Sujadi; Dadan Zaliluddin; Tri Ferga Prasetyo; Ii Sopiandi (Universitas Majalengka, 2022)
The community as one of the elements of the nation utilizes digital connectivity in order to connect Indonesia with a mindset, global business opportunities, and a new future. Indonesia's digital transformation is realized by preparing digital talent as the main driver of productive use of digital connectivity. Modern society is currently faced with the challenges of using the internet and digital media that are useful as well as opportunities for various problems. Cakap with Digital Media is one of the programs from the Ministry of Communication and Information to improve the community's ability to deal with disruption. Through the Office of Communication and Information Technology of West Java Province, these activities are outlined in several activities, one of which is Digital Village through Jabar Digital Service (JDS) activities. Based on a survey on the implementation of internet infrastructure assistance (Tower Desa), there are several areas that have been built, one of which is the Argapura Bumi Mandiri area which consists of 14 (fourteen) villages. The Ministry of Communication and Information Technology's Digital Literacy activities will continue to be pursued through Digital Media Cakap training activities in the Argapura Bumi Mandiri area.